2017
DOI: 10.1007/s40279-017-0720-4
|View full text |Cite
|
Sign up to set email alerts
|

A Social Identity Approach to Understanding and Promoting Physical Activity

Abstract: Against the backdrop of a global physical inactivity crisis, attempts to both understand and positively influence physical activity behaviours are characterized by a focus on individual-level factors (e.g. cognitions, attitudes, motivation). We outline a new perspective, drawn from an emerging body of work exploring the applicability of social identity and self-categorization theories to domains of sport and health, from which to understand and address this pervasive problem. This social identity approach sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
127
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(147 citation statements)
references
References 104 publications
14
127
3
3
Order By: Relevance
“…Both increased self-esteem and social support appeared to mediate the association between higher perceived mentor support and increased wellbeing. It has been previously suggested that mentors who represent, advance, create and embed a shared sense of social identity can aid participation in physical activity [64]. Even though this was not supported here regarding MVPA, our results suggest that this may extend to wellbeing.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Both increased self-esteem and social support appeared to mediate the association between higher perceived mentor support and increased wellbeing. It has been previously suggested that mentors who represent, advance, create and embed a shared sense of social identity can aid participation in physical activity [64]. Even though this was not supported here regarding MVPA, our results suggest that this may extend to wellbeing.…”
Section: Discussioncontrasting
confidence: 88%
“…Concerns around masculine and feminine ideologies of health-related behaviour and body image are very relevant to physical activity promotion in a school setting but are rarely central to physical activity provision in schools. It follows that considering social identity in physical activity promotion may have particular value in schools as it has been proposed to have the potential to facilitate the promotion of exercise behaviour, to impact physical activity norms positively and this also has been identified as facilitating successful mentorship [64]. We previously proposed that boys' opinions may hold more weight in the class environment [25].…”
Section: Discussionmentioning
confidence: 99%
“…13,16,17 As such, they add to growing evidence for the benefits of favorable group environments for promoting physical activity, and further demonstrate the impact of social factors on individuals' physical activity behaviors. 40 Our hope is that the findings reported here stimulate greater attention to the importance of leaders in physical activity settings, and, in particular, lay the foundation for (a) causal examinations of the effects of identity leadership in physical activity settings (eg, using longitudinal and experimental designs), and (b) attempts to implement the principles of identity leadership in physical activity settings (eg, through interventions).…”
Section: Perspectivesmentioning
confidence: 79%
“…Building on these promising findings, recent research has examined the role that physical activity leaders can play in fostering members' group identification, and thus greater rates of attendance in group sessions (Stevens, Rees, Coffee, et al, 2018). Extending growing evidence from organizational (Steffens, Yang, Jetten, Haslam, & Lipponen, 2017), political (Steffens & Haslam, 2013) and sports performance (Slater & Barker, 2018) domains, this research points to the benefits of leaders engaging in identity leadership (Haslam et al, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…That is, leaders acting to represent, advance, create, and embed an identity that is shared by members of the particular group they lead (Haslam et al, 2011;Steffens et al, 2014). Specifically, in addition to providing further evidence of a positive relationship between individuals' sport or exercise group identification and their participation in grouprelevant activity, researchers have found (1) a positive association between group members' perceptions of their leaders' engagement in identity leadership and their own group identification, and (2) that the positive relationship between members' perceptions of their leaders' engagement in identity leadership and members' attendance is mediated by their group identification (Stevens, Rees, Coffee, et al, 2018). Moreover, these effects have been observed for multiple facets of identity leadership, providing preliminary evidence that physical activity leaders should strive (1) to represent and embody the particular qualities and attributes that define the group and set it apart from other groups (i.e., be seen as a prototypical group member), (2) to champion the group's identity and interests (i.e., to be seen to engage in identity advancement), (3) to play an active role in creating and shaping the group's identity and a collective sense of 'we' and 'us' (i.e., to act as identity entrepreneurs), and (4) to devise activities that make the group matter, and allow its shared identity to be lived out (i.e., to act as identity impresarios).…”
Section: Theoretical Frameworkmentioning
confidence: 99%